Essays on Asset Pricing - Christian Skov Jensen (Copenhagen Business School (CBS), 2018)
The central formula in asset pricing relates the price of an Arrow-Debreu security to an investor's preferences and beliefs: Price of an Arrow-Debreu security = Preferences Beliefs. We observe the prices of Arrow-Debreu securities in the option markets. But we do not directly observe the extent to which these prices are driven by preferences or beliefs. Decomposing and investigating preferences and beliefs is essential for understanding asset prices, and it is therefore the focus of this thesis. In chapter one, my co-authors and I develop a model in which we can disentangle the contribution in asset prices which is driven by preferences and beliefs. In chapter two, my co-author and I estimate investor beliefs and study how these beliefs vary over time. In chapter three, I estimate investor preferences and study how they co-vary with investor beliefs.
hdl:10398/9653
Keywords: 650